Impact of comorbid heart failure among hospitalized patients with sarcoidosis: A United States population-based cohort study - Bruce Adrian Casipit; Kevin Bryan Lo; Carlo Gabriel Casipit; Abdiodun Idowu; Aman Amanullah (International Journal of Cardiology: Heart & Vasculature, 2023)
Background: There is paucity of data regarding the impact of concomitant heart failure (HF) on the in-hospital outcomes among hospitalized sarcoidosis patients. We aim to investigate the factors associated with concomitant HF and its impact on in-hospital outcomes among hospitalized sarcoidosis patients. Methods: We utilized the 2018–2020 National Inpatient Sample (NIS) Database in conducting this study. Multivariable logistic and linear regression models were used to examine the factors associated with HF and hospital-associated outcomes among patients with sarcoidosis. Results: A total of 36,864 hospitalized patients with sarcoidosis were identified, of which 24.78 % (n = 9135/36,864) had concomitant HF. Factors associated with concomitant HF were age (aOR 1.03; 95 % CI: 1.02–1.03, p value ≤ 0.001), black race (aOR 1.74; 95 % CI: 1.47–2.05, p value ≤ 0.001), not being female (aOR 0.79; 95 % CI: 0.69–0.91, p value ≤ 0.001), and arrhythmias (aOR 2.50; 95 % CI: 2.10–2.98, p value ≤ 0.001) specifically atrial fibrillation and ventricular tachycardia. Comorbidities associated with concomitant HF in this population were hyperlipidemia, obesity, coronary artery disease, cardiac device implantation history, and chronic kidney disease stage 1–4. Concomitant HF was not an independent predictor of in-hospital mortality or length of stay (LOS). However, age (aOR 1.04; 95 % CI, 1.03–1.06; p ≤ 0.001) and arrhythmia burden (aOR 2.08; 95 % CI, 1.47–2.95; p ≤ 0.001), specifically ventricular tachycardia and fibrillation, were independently associated with in-hospital mortality among sarcoidosis patients. Conclusion: Traditional cardiovascular risk factors were associated with concomitant HF among hospitalized sarcoidosis patients. Moreover, concomitant HF among sarcoidosis patients was not significantly associated with in-hospital mortality or LOS.